Achilles’ complex and children’s creativity - Carlo Bellieni (Bioethics Update)
Background: Living in a family with examples of love and hard work is often thought to be a key factor in the development of creativity. This is not always the case. Objective: To assess the roots of creativity in different family environments. Methods: We analyzed the available literature on the development of childhood creativity, focusing on the correlation between an early dysfunctional family (FD) and the presence/absence of creativity. Results: In FD, creativity is sometimes due to children’s difficulty in surviving environmental adversities; this creates a world of manic activity that serves to counteract the violence of the real world. In this world, the child deepens talents, but often with the side effect of developing asocial or neurotic traits. Conclusions: FD can paradoxically forge geniuses. The “Achilles’ Complex” is a paradigm of this process that will be explained in the text.